Lungfish tooth plates (Sarcopterygii, Dipnoi) from the Late Cretaceous (Santonian) Eutaw Formation of Alabama and Mississippi, USA. (26th December 2018) - Harrell, T. Lynn; Ehret, Dana J.
Abstract: Lungfish are a poorly represented component of the Mesozoic fossil record in North America, as most lungfish fossils consist of rare, isolated dental plates that are of little diagnostic value due to their conservative nature. In eastern North America, the paucity of lungfish fossils in Late Cretaceous strata is further compounded by the occurrence of geologic units that are primarily marine in origin, unlike the Late Jurassic to mid-Cretaceous fluvial deposits of the American west that contain comparatively more specimens. Lungfish fossils from the eastern side of the Late Cretaceous Western Interior Seaway (Appalachia) have previously been reported from the Cenomanian Woodbine Formation of northeast Texas and the Campanian Mount Laurel Formation of New Jersey. Here we report two new occurrences of eastern North American lungfish tooth plates from the Santonian Eutaw Formation of Alabama and Mississippi. These two specimens are referred to Ceratodus frazieri Ostrom, 1970 and Ceratodus carteri Main et al., 2014, species that are better known from the mid-Cretaceous of the Western Interior of North America. This discovery is the first published record of lungfish of any age from the states of Alabama and Mississippi. It partially bridges the temporal gap in the fossil record between the Cenomanian lungfish of Texas and the Campanian lungfish of New Jersey and extends the biogeographic range of Late Cretaceous lungfish to the eastern Gulf Coastal Plain of the United States.